2019
DOI: 10.1016/j.jns.2019.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Fall risk in stroke survivors: Effects of stroke plus dementia and reduced motor functional capacity

Abstract: Background: Despite extensive research on falls among individuals with stroke, little is known regarding the impact of neurological conditions with comorbid diagnoses and motor functional capacity on the risk of falls in these individuals. Hence, the purpose of this study was to determine the fall risk and the contribution of reduced motor functional capacity to fall risk in individuals with stroke, dementia, and stroke plus dementia.Methods: Data from the National Health and Aging Trends Study (NHATS), a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…The balance impairment in the poststroke state is complex. It includes weight-bearing asymmetry (WBA), 1À7 muscle weakness, 8 disturbed perception, 9 destroyed ankle proprioception, 10 cognitive failure 11,12 and in consequence an increased visual dependency. 9,13 All of these factors lead to postural instability and finally to falls.…”
Section: Introductionmentioning
confidence: 99%
“…The balance impairment in the poststroke state is complex. It includes weight-bearing asymmetry (WBA), 1À7 muscle weakness, 8 disturbed perception, 9 destroyed ankle proprioception, 10 cognitive failure 11,12 and in consequence an increased visual dependency. 9,13 All of these factors lead to postural instability and finally to falls.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure ulcers are the long-term compression of local skin or soft tissues and then a kind of ischemia, hypoxia, or malnutrition ulcer necrosis, and it is one of the common complications of patients with coma, hemiplegia, or postural restriction caused by ICH ( 11 ). Falls are more common in patients with impaired motor and cognitive function and are also an important mechanism of injury leading to ICH ( 12 , 13 ). During the nursing period of this study, the incidence of pressure sores and falls in the study group were significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also found a relationship between functionality and either the risk of falling and/or the occurrence of falls, regardless of the scale used to assess functionality. 33 , 36 39 …”
Section: Discussionmentioning
confidence: 99%